Variabel – Variabel Yang Mempengaruhi Struktur ModalPada Perusahaan Manufaktur Di Bursa Efek Indonesia - Kurnia Murni Utami; Diana Dwi Astuti; Hamzah Fansuri Yusuf (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2020)
This study aims to determine the effect of simultaneous and partial variables of sales stability, asset structure, operating leverage, company size, and profitability on capital structure in manufacturing companies on the Indonesia Stock Exchange. Research period 2014 - 2018. Determination of the sample by purposive sampling method. Using the method of multiple linear regression analysis. The results of the classic assumptions of the study, showed that normally distributed, no multicollinearity, no symptoms of heteroscedasticity, and no autocorrelation. The results of multiple regression, show the independent variables simultaneously influence the dependent variable. Partially, the variables of sales stability, operating leverage and firm size have a significant effect on capital structure, while asset structure and profitability have no significant effect on capital structure.